Stock Trading on the Stock Exchange in the Perspective of Islamic Law - Arafah, Muh.; Jasmani, A.; Fadlang, Muhammad (Al-Bayyinah, 2024)
One form of investment that can be done in today's economy is trading stocks on the stock exchange. This paper aims to describe the ability to trade stocks on the stock exchange and the benefits obtained for those who invest in the stock exchange in the form of stocks, the study also discusses the side of Islamic law, as part of the law of stock trading on the stock exchange. This paper uses a literature study method that takes references from various sources of writing related to the problems raised. The source of data in this study refers to literature studies that discuss stocks, stock exchanges, and Islamic law. The results of this study show that investing in stocks on the stock exchange gives benefits to those who invest in stocks in the form of stock returns, including capital gains, dividends, and other company shares as measured by the company's performance. Meanwhile, in the perspective of Islamic law, stock trading on the stock exchange or investing is allowed, because in principle it uses a sale and purchase contract or called bai' al-musawamah, in the process it does not carry out trading actions such as tadlis, najsy, ikhtikar, bai ma'dum and riba, as stipulated in the fatwa of DSN MUI No. 80 of 2011.